2020
DOI: 10.2147/opto.s275071
|View full text |Cite
|
Sign up to set email alerts
|

<p>Knowledge of Childhood Blindness and Associated Factors Among Parents or Guardians in Maksegnit Town, Northwest Ethiopia</p>

Abstract: Introduction: Childhood blindness is defined as a group of eye diseases occurring in childhood or early adolescence. Good parental knowledge of childhood blindness is important for early detection and management of the lifelong burden. Purpose: This study aimed to assess knowledge of childhood blindness and associated factors among parents or guardians. Materials and Methods: A community-based cross-sectional study was conducted. Systematic random sampling was used to select the study participants. Data were c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 16 publications
0
1
1
Order By: Relevance
“…The current study found that most of the participants have sufficient knowledge about childhood eye problems with the highest awareness and knowledge score obtained for blurry vision and refractive errors respectively. This finding of sufficient knowledge is contrary to previous findings reported among parents in low-income countries such as Ethiopia (17) and Nigeria who had low level of knowledge ( 18), but similar to those reported among parents in Saudi Arabia, the emerging high-income country (12) suggesting the influence of economic development of a country on the level of health-related knowledge.…”
Section: Discussioncontrasting
confidence: 94%
See 1 more Smart Citation
“…The current study found that most of the participants have sufficient knowledge about childhood eye problems with the highest awareness and knowledge score obtained for blurry vision and refractive errors respectively. This finding of sufficient knowledge is contrary to previous findings reported among parents in low-income countries such as Ethiopia (17) and Nigeria who had low level of knowledge ( 18), but similar to those reported among parents in Saudi Arabia, the emerging high-income country (12) suggesting the influence of economic development of a country on the level of health-related knowledge.…”
Section: Discussioncontrasting
confidence: 94%
“…Parental knowledge on childhood eye problems has been reported in several countries with different economic status and cultures; these two are among the factors that may influence level of health-related knowledge and health seeking behaviour (16). Aseefa et al (17) reported that the overall level of knowledge among parents in Ethiopia on the causes, prevention and treatment options of childhood blindness was considered low; with only one-third of the respondents had good level of knowledge. On the other hand, a study in an urban area in Nigeria reported that parents had a high level of knowledge and awareness about cataract and red eye, which was however lower for amblyopia (18).…”
Section: Introductionmentioning
confidence: 99%